The use of geoprocessing in planning sustainable production systems in pastures (Semiárida, 2020)
Livestock production in pastures have deserved increasing interest in modern society, which is more concerned about environmental issues. This study aimed to validate the use of geoprocessing tools to aid the planning, implementation and utilization of intensive pasture systems in order to boost plant growth and prolong the period of use of pasture with better quality, ensuring not only greater income to the producer, but also increased conservation and recovery of grazing lands. This work was conducted in the city of Viamão, RS, Brasil, from June to November 2011, in areas with different uses (pastures, grasslands, reforestation areas). The GPS receivers were employed to survey points of the field. The data files were downloaded in TrackMacker® software to elaborated planimetric maps, performed with the help of GOOGLE EARTH® program. Then, the latitude, longitude and altitude were interpolated in software GOLDEN SURFER® 10, obtaining, thereby, planialtimetric maps. Based on these information, we made the subdivision of the pastures, considering the effective grazing surface, land slope and the access to water. We also defined exclusion areas; selected points for installation of new areas of water; collected soil material; and observed three cycles of use (an average of two days of permanence, followed by twenty days of rest) from different areas. These tools do not exclude the need for direct observation and monitoring, however, when they are properly employed, they act as facilitators, enabling a faster and more accurate management decisions.
Keywords: Geoprocessing tools; Pastoral planning; Rotational grazing; Agro-silvopastoral system; Sustainability; Land use